Georgia Architectural and Historic Properties Survey of Barney [07] Unknown, Cecil, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Barney [07] Unknown, Cecil, Ga. December 1980. A one story L-shaped plan with gabled roof and shiplap siding. Shed porch with square posts. Sash windows with 2/2 lights. Transom. Brick piers (filled in). Good condition. Date of Construction: c. 1910. Not significant as part of a potential National Register historic district. Town not extensive enough for a district.
Georgia Architectural and Historic Properties Survey of Barney [07] Unknown, Cecil, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 902 KB (923,864 bytes).
Keywords: Historic buildings; Lowndes County Historical Society (Lowndes County, Ga.); Real property surveys; Brooks County (Ga.); Barney, Ga.; Cecil, Ga.